Iron Deficiency Anaemia Caused by Nonspecific (Idiopathic) Small Bowel Ulceration: An Uncommon Presentation of an Uncommon Disease - Gabriele Capurso; Edith Lahner; Nadia Pallotta; Francesco Panzuto; Gianfranco Delle Fave; Bruno Annibale (Canadian Journal of Gastroenterology)
Ulcers of the small bowel are rare, and in most cases are due to infections, inflammatory bowel diseases, malignancies or drugs. When none of these causes is recognized, they are classified as ‘nonspecific’ or idiopathic. Such lesions are uncommon, and in most cases present with occlusion. A case of a middle-aged woman with iron deficiency anemia due to occult bleeding, with negative gastroscopy and colonoscopy is presented. The diagnosis of a small bowel pathology resembling Crohn’s disease was made by small bowel follow through and small intestine contrast ultrasonography. An ileal ulcer was identified at surgery, and after resection the patient experienced a stable recovery from the anemia without ulcer recurrence. Neither histology nor clinical or biochemical features suggested the diagnosis of an inflammatory bowel disease. Other possible causes were unlikely and the lesion was therefore diagnosed as idiopathic. This report also focuses on the need and the modality to investigate the small bowel in iron deficiency anemia patients.